Pathophysiological Mechanisms in Sclerosing Skin Diseases - Eckes, Beate; Wang, Fang; Moinzadeh, Pia; Hunzelmann, Nicolas; Krieg, Thomas (Frontiers in Medicine, 2017)
Sclerosing skin diseases represent a large number of distinct disease entities, which include systemic sclerosis, localized scleroderma and scleredema adultorum. These pathologies have a common clinical appearance and share histological features. However, the specific interplay between cytokines and growth factors, which activate different mesenchymal cell populations and production of different extracellular matrix components, determines the biomechanical properties of the skin and the clinical features of each disease. A better understanding of the mechanisms underlying these events is prerequisite for developing novel targeted therapeutic approaches.